The effect of leadership style and job stress on the performance of Ukrida Hospital employees with job satisfaction as a mediating variable - Ronald Prawira; Adrie Frans Assa (Global Academy of Multidisciplinary Studies, 2025)
Purpose: This study examines how leadership style and job stress influence employee performance at Ukrida Hospital, with job satisfaction as a mediating variable. Methodology: A quantitative survey was conducted with 134 permanent employees (tenure >6 months). Data were analyzed using Structural Equation Modeling (SEM-PLS). Results: Leadership style positively affects job satisfaction and performance. Job stress also shows a positive effect on both job satisfaction and employee performance. Job satisfaction further enhances performance and significantly mediates the effects of leadership style and job stress. These findings indicate that challenge-related stress can improve employee outcomes. Conclusion: The study provides empirical evidence that effective leadership styles and well-managed work stress can enhance job satisfaction and employee performance at Ukrida Hospital. The results highlight the importance of leadership strategies and stress management practices in improving the quality of human resources. Limitations: The research is limited to one hospital, uses a cross-sectional survey design, and focuses only on employees with more than six months of tenure. These factors may restrict generalizability and the ability to infer long-term causal relationships. Contribution: This study contributes to the literature by demonstrating the dual role of job stress when perceived as a challenge in improving satisfaction and performance, and by confirming the mediating function of job satisfaction in healthcare organizational settings. It also offers practical insights for hospital management in designing leadership and stress-management interventions to improve employee outcomes.